2016
DOI: 10.1016/j.comppsych.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of multiple gene variants and their effects on schizophrenia phenotypes

Abstract: The interaction of specific susceptibility genes is likely to lead to specific clinical sub-phenotypes of schizophrenia. Larger patient cohorts with more extensive clinical data will improve the detection of gene interactions and the resultant schizophrenia clinical phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Although our findings provide a rationale for broadening the discussion of EOS differences beyond age alone (≤12 or ≥13), other investigators would need to replicate and validate these findings before they could be considered consistently identifiable “subtypes” of EOS. Cluster analysis has been previously used by numerous investigators searching for ways to harness the heterogeneity of individuals diagnosed with schizophrenia‐spectrum disorders across the life span to provide a useful platform for more effective treatment strategies: cognitive subgroups based on differential brain volumetric reductions and cognitive decline (Weinberg et al, ); interaction of multiple gene variants and their effects on schizophrenia phenotypes (Cheah et al, ); social cognition subgroups (Rocca, Galderisi, Rossi, et al, ); functional outcomes across subgroups of adults (Rocca et al, ); and cognitive profiles of subgroups based on neuropsychological measures (Reser, Allott, Killackey, Farhall, & Cotton, ) among many others over the past two decades.…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings provide a rationale for broadening the discussion of EOS differences beyond age alone (≤12 or ≥13), other investigators would need to replicate and validate these findings before they could be considered consistently identifiable “subtypes” of EOS. Cluster analysis has been previously used by numerous investigators searching for ways to harness the heterogeneity of individuals diagnosed with schizophrenia‐spectrum disorders across the life span to provide a useful platform for more effective treatment strategies: cognitive subgroups based on differential brain volumetric reductions and cognitive decline (Weinberg et al, ); interaction of multiple gene variants and their effects on schizophrenia phenotypes (Cheah et al, ); social cognition subgroups (Rocca, Galderisi, Rossi, et al, ); functional outcomes across subgroups of adults (Rocca et al, ); and cognitive profiles of subgroups based on neuropsychological measures (Reser, Allott, Killackey, Farhall, & Cotton, ) among many others over the past two decades.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of titles and abstracts resulted in the exclusion of 1231 articles. In total, 61 articles were selected for full-text review, and eight articles [44][45][46][47][48][49][50][51] were excluded due to unclear outcomes, mixed diagnosis of the study population and use of a nonstatistical method of clustering or clustering based on different phenotypes of schizophrenia. Finally, data were extracted from 53 longitudinal and cross-sectional studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…These gene-gene interactions may cause network ripple effects among the connected genes that amplify the impact of small individual VAOs. Others have observed a similar phenomenon among risk genes for schizophrenia (Cheah et al 2016;Su et al 2017). Furthermore, this notion is similar to that of Greenspan (2001) who described the functional connectivity of gene networks in terms of exibility and pleiotropy.…”
Section: Discussionmentioning
confidence: 54%
“…Davierwala et al (2005) reported that essential genes are much more interactive than non-essential genes and schizophrenia risk genes are highly enriched for ones that are essential for life and broadly conserved during evolution (Kasap et al 2018). Consequently, we hypothesized that risk genes for schizophrenia are similarly more interactive than random genes, which may amplify the effect sizes of interacting variants (Cheah et al 2016). If so, the ndings would highlight the importance of being able to account for gene-gene interactions in models of genetic liability for heritable psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%